Pemilihan Lokasi Prioritas Pelayanan Penyaluran Air Limbah di Kabupaten Cianjur Dengan Metode Skoring dan Pembobotan - Eka Wardhani; Habib Ali Rais (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
The increase in population in Cianjur Regency has begun to be significant. Inadequate urban sanitation systems make people dispose of their domestic waste carelessly into the nearest river or water body resulting in environmental pollution. One way to reduce these problems is to build an adequate domestic wastewater distribution system. The planning of a domestic wastewater distribution system in an area must be accompanied by the selection of the best location to increase the effectiveness of environmentalpollution prevention. Priority service areas are selected based on 5 available criteria, namely: Population density, Topography, Clean water distribution network, Sanitation condition, and Slum area. The method of determining priority areas used is the scoring and weighting method. The results obtained are 3 priority zones so that it can be determined which sub-district is the planning area, namely Cianjur District